A 3D Printed Device for Easy and Reliable Quantification of Fungal Chemotropic Growth - Schunke, Carolin; Pöggeler, Stefanie; Nordzieke, Daniela Elisabeth (Frontiers in Microbiology, 2020)
Chemical gradients are surrounding living organisms in all habitats of life. Microorganisms, plants and animals have developed specific mechanisms to sense such gradients. Upon perception, chemical gradients can be categorized either as favorable, like nutrients or hormones, or as disadvantageous, resulting in a clear orientation towards the gradient and avoiding strategies, respectively. Being sessile organisms, fungi use chemical gradients for their orientation in the environment. Integration of this data enables them to successfully explore nutrient sources, identify probable plant or animal hosts, and to communicate during sexual reproduction or early colony development. We have developed a 3D printed device allowing a highly standardized, rapid and low-cost investigation of chemotropic growth processes in fungi. Since the 3D printed device is placed on a microscope slide, detailed microscopic investigations and documentation of the chemotropic process is possible. Using this device, we provide evidence that germlings derived from oval conidia of the hemibiotrophic plant pathogen Colletotrichum graminicola can sense gradients of glucose and reorient their growth towards the nutrient source. We describe in detail the method establishment, probable pitfalls, and provide the original program files for 3D printing to enable broad application of the 3D device in basic, agricultural, medical, and applied fungal science.